2019
DOI: 10.1007/s40430-019-1688-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscous dissipation and Joule heating on MHD radiative tangent hyperbolic nanofluid with convective and slip conditions

Abstract: The forthright intention of this communication is to scrutinize the effect of variable thermal conductivity and thermal radiation on the magnetohydrodynamic tangent hyperbolic fluid in the presence of nanoparticles past a stretching sheet. For heat and mass transport phenomena, the collective stimulus of slip and convective conditions with the internal heating, viscous dissipation and Joule heating have been taken into account. The boundary layer equations of two-dimensional tangent hyperbolic nanofluid have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Since we have considered the steady-state flow problem, therefore, time derivative terms disappear. The continuity, momentum, thermal heat, concentration, and gyrotactic microorganism's equations are expressed as [21,37,44].…”
Section: Physical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we have considered the steady-state flow problem, therefore, time derivative terms disappear. The continuity, momentum, thermal heat, concentration, and gyrotactic microorganism's equations are expressed as [21,37,44].…”
Section: Physical Modelmentioning
confidence: 99%
“…where σ * * is the Stefan-Boltzmann constant while k * * represents the mean absorption coefficient. Before computing the numerical solution, let us convert the flow equations in dimensionless form by inserting the following variables [21,37,43,44].…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Tangent hyperbolic nanofluid models constitute a recent development in heat and mass transfer fluids in boundary layer flows. The model takes into account the shear thinning and thickening behavior of the fluid, Hayat et al The boundary layer flow of a MHD tangent hyperbolic nanofluid over a stretching sheet was studied by Khan et al The application of the generalized Fourier heat law to the flow of tangent hyperbolic liquids over a sheet stretching nonlinearly was studied by Waqas et al Recent studies on MHD tangent hyperbolic flows can be found in References .…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of thermal radiation plays a vital role in the heat and mass transfer, and researchers conducted many studies to highlight its importance. For further study, see details in [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%